Allele-Specific Mechanisms Guide Salvage Therapy to Overcome Daraxonrasib Resistance in Pancreatic Cancer - Daniel Dorbin; Juliannie Herrera; Raven Davidson; Naveen Kumar Chandrashekar; Gabrielle Scheuber; Priyanga Jayakrishnan; Christabelle Rajesh; Grayson Johnson; Jason Yuan; Matthew A. Sochor; John F. Langenheim; Mohammed Aldakkak; et al. (Cancer Research, 2026)
Abstract Clinical-grade RAS inhibitors raise an unresolved question as to whether KRAS alleles impose constraints on adaptive resistance that can be exploited therapeutically. Using daraxonrasib (RMC-6236), a multi-selective RAS(ON) inhibitor, we compared resistance mechanisms between KRASG12D and KRASG12R, mutants with fundamentally different RAS network dynamics. Daraxonrasib inhibited KRASMUT primarily through steric occlusion of effector binding, while engaging RASWT only modestly (~20%). KRASG12R was marked by its inability to transactivate RASWT, and daraxonrasib resistant KRASG12R PDAC cells utilized EGFR/RASWT-GTP signaling as the dominant adaptive route. In contrast, KRASG12D resistance arose through retained KRASG12D-GTP signaling, with a decrease of cyclophilin A (CypA) protein, the binding partner required for daraxonrasib activity. The shift from KRASG12R dependence to EGFR/RASWT dependence conferred sensitivity to trametinib. As clinical confirmation, a KRASG12R PDAC patient who progressed after 10 months on daraxonrasib showed intratumoral EGFR/RASWT activation, and rapid 3D-bioprinted patient-derived tumoroid modeling predicted sensitivity to trametinib-based combination therapy. Despite the aggressive disease trajectory and lack of response to the two immediately preceding lines of therapy, sixth-line trametinib-based combination therapy achieved approximately 5 months of disease control, and this patient ultimately achieved 40 months of overall survival, far exceeding the 8–12 month median for metastatic PDAC. Collectively, these data establish a framework in which allele-specific RAS network topology dictates the adaptive resistance landscape, enabling rational selection of targeted therapies with meaningful clinical benefit in metastatic PDAC.